Scheduled Postoperative Ketorolac Does Not Decrease Opiate Use following Free Flap Breast Reconstruction - Sudduth, Jack D.; Moss, Whitney D.; Clinker, Christopher; Marquez, Jessica L.; Anderson, Eric; Eddington, Devin; Agarwal, Jayant; Kwok, Alvin C. (Journal of Reconstructive Microsurgery, 2023)
Background In the setting of the opioid crisis, managing postoperative pain without the exclusive use of opiates has become a topic of interest. Many hospitals have begun implementing enhanced recovery after surgery protocols to decrease postoperative complications, hospital costs, and opiate utilization. Ketorolac has been added to many of these protocols, but few studies have examined its effects independently.Methods A retrospective chart review was performed on all patients that received autologous breast reconstruction from October 2020 to June 2022 at an academic institution. We identified patients who did and did not receive postoperative ketorolac. Use of ketorolac was based upon surgeon preference. The two groups were compared in basic demographics, reconstruction characteristics, length of stay, complications, reoperations, and morphine milligram equivalents (MMEs).Results One-hundred ten patients were included for the analysis, with 55 receiving scheduled postoperative ketorolac and 55 who did not receive ketorolac. There were seven incidences of postoperative complications in each group (12.7%, p = 1.00). The total mean postoperative MMEs were 344.7 for the nonketorolac group and 336.5 for the ketorolac group (p = 0.81). No variable was found to be independently associated with postoperative opiate use. Ketorolac was not found to contribute significantly to any postoperative complication.Conclusion In this study, the use of ketorolac did not significantly reduce opiate use in a cohort of 110 patients. Surgeons should consider whether the use of ketorolac alone is the best option to reduce postoperative opiate use following free flap breast reconstruction.
Keywords: opiates; ketorolac; ERAS; pain control; postoperative pain; breast reconstruction